Microvascular Decompression for Concurrent Trigeminal Neuralgia and Hemi-Laryngopharyngeal Spasm: A Case Report. Issue 2 (2nd February 2023) - Katayama, Michiru; Noro, Shusaku; Asayama, Bunsho; Amano, Yuki; Okuma, Masahiro; Honjo, Kaori; Seo, Yoshinobu; Nakamura, Hirohiko
Abstract : BACKGROUND AND IMPORTANCE: Hemi-laryngopharyngeal spasm (HeLPS) may result from vascular compression of the vagus nerve and can be treated using microvascular decompression. We describe the clinical characteristics and surgical treatment in a case of concurrent trigeminal neuralgia (TN) and HeLPS. CLINICAL PRESENTATION: A 44-year-old man presented with a 12-month history of right TN and 8-month history of intermittent episodes of repeated throat contractions associated with a very distressing choking sensation. Preoperative 3-dimensional fusion imaging demonstrated compression of the trigeminal nerve by the superior cerebellar artery and petrosal vein and compression of the vagus nerve by the posterior inferior cerebellar artery and one of its branches. Microvascular decompression was performed by a right standard retrosigmoid approach with enlarged craniotomy. Initially, the compression of the trigeminal nerve was identified by visual inspection. All the offending vessels were wrapped in Teflon felt, transposed away from the trigeminal nerve, and adhered to the tentorial membrane and petrous bone using fibrin glue. Furthermore, observation of the caudal rootlets of the vagus nerve revealed that the posterior inferior cerebellar artery and its branch compressed the ventral side of the nerve. These vessels were displaced antero-caudally with Teflon felt and fibrin glue; no other vessels were found around the trigeminal and vagus nerves. Postoperatively, the patient had immediate and complete resolution of symptoms of TN and HeLPS without recurrence at the 18-month follow-up. CONCLUSION: HeLPS may occur with TN, and neurosurgeons should identify the symptoms suspicious of this disease preoperatively.